“Aroeira” (Myracrodruon urundeuva) methanol extract: the relationship between chemical compounds and cellular effects - Machado, Alessandra Cury; Souza, Leonardo Perez [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Pieroni, Laís Goyos [UNESP]; Matos, Adriana Arruda; Oliveira, Flávia Amadeu de; Vilegas, Wagner [UNESP]; Damante, Carla Andreotti; Dokkedal, Anne Lígia [UNESP]; Oliveira, Rodrigo Cardoso de (Taylor & Francis, 2016)
Context: “Aroeira” [Myracrodruon urundeuva Allemão (Anacardiaceae)] is a tree whose leaves have been studied for therapeutic purposes in medicine and dentistry. Objective: The study chemically identifies the leaf extract of aroeira and determines its effect on human gingival fibroblasts. Materials and methods: An 80% methanol leave extract was obtained by maceration and chemically identified through flow-injection analysis–electrospray ionization–ion trap–tandem mass spectrometry (FIA–ESI–IT–MSn). Cytotoxicity of the aroeira’s methanol extract was evaluated in lineage of fibroblasts. Adherent cells were treated with different concentrations of aroeira’s methanol extract in the medium: 0.1, 1, 10, 100 and 1000 μg/mL. Control cells were cultivated in the medium only. Analyses were done at 24, 48, 72 and 96 h of culture by neutral red assay; and at 24, 48 and 96 h by crystal violet assay. Results: FIA–ESI–IT–MS analysis determined the presence of compounds, for the first time in the species: quercetin-O-glucuronide and quercetin-O-deoxyhexose-O-glucose in the extract. On one hand, neutral red and crystal violet assay showed a reduction (to 50% up until 100%) of cellular viability of groups of 100 and 1000 μg/mL compared with control at 96 h (p < 0.05). On the other hand, lower concentrations (0.1; 1 and 10 μg/mL) of the extract were similar to that of the control at 96 h (p < 0.05), in general. Conclusions: In view of the results, we can conclude that the extract of aroeira presents tannins and flavonoids. Furthermore, the extract is capable of modulating the viability of human gingival fibroblasts according to its concentration.
Keywords: Anarcadiaceae; cellular viability; cytotoxicity; medicinal plants